(untitled) (Contemporary Journal of Social Science Review, 2025)
In this rapid technological growth, the flipped classroom is gaining more attention and acceptance in education. The primary purpose of this study was to investigate the effects of flipped classroom instruction on science achievements in primary education. This was an experimental study; a sample of 60 5th-grade students participated. The average age of the students was between 12 and 13 years. A pre- and post-test was administered to obtain the results. Data collection took place for five working weeks (April and May). The results indicate that flipped classroom instruction significantly enhances primary students’ performance in science compared to traditional teaching approaches. Students in the experimental group, who engaged with pre-class video content and participated in active problem-solving activities during class, showed greater achievement levels than those in the control group.